SYNTHESIS AND CHARACTERIZATION OF CdS IN DIOL VANILIN LIQUID CRYSTAL MONOMER - H. L. Lee; M. Abu Bakar; J. Ismail; A.M. Issam (Universitas Gadjah Mada, 2007)
Nanocomposites comprising diol-vanilin and cadmium sulfide (CdS) has been synthesized via chemical precipitation method in ethanol at refluxed temperature (160 oC) for 12 hours. CdCl2. 2.5H2O and thiourea as cadmium and sulfide precursors respectively were employed. Diol vanilin is a thermotropic liquid crystal monomer which exhibits enantiotropic nematic metaphase texture when observed under polarizing microscope and confirmed by DSC thermal stability study. A series of different mass composition of diol vanilin and CdS nanocomposites ranging from 0.1:1.0 till 1.0:1.0(w/w) were prepared and characterized using XRD, TEM, SEM-EDX, POM and DSC. The X-ray diffraction pattern (XRD) showed broad peaks due to the formation of cubic CdS nanoparticles in diol vanilin matrix. The nanocomposites at low mass composition of CdS still maintained their nematic phase. However, the liquid crystal property was affected when the mass composition of CdS in nanocomposite was increased and the liquid crystal characteristic vanished when the mass composition was at 0.6:1.0.